Membaca Krisis Lingkungan Melalui Lensa Tafsir Ekologi: Analisis QS. al-Rūm [30]: 41 - Putri, Lintang Dewi Fi'liya; Ahmadi, Brillian Zaki Ramadhan; Aulia’, Kamailia Karimatul (Institut Agama Islam Negeri Kediri, 2025)
The worsening environmental crisis has become a global concern, necessitating in-depth studies from various perspectives, including those from a religious perspective. This research aims to examine the environmental crisis through the lens of ecological exegesis of QS. al-Rūm [30]: 41 by referring to several classical and contemporary tafsīr. QS. al-Rūm [30]: 41 highlights the destruction of land and sea caused by human actions, yet it is often understood only textually without exploring its ecological implications. This study aims to interpret the verse through an ecological exegesis approach, comparing and analyzing the views of classical and contemporary exegetes to uncover the concept of environmental degradation, along with its theological and practical implications. Thus, Qur’anic values can serve as a foundation for Islamic ecological ethics in responding to the global environmental crisis in a sustainable manner. Employing a qualitative method and library research, data from classical and contemporary tafsīr are thoroughly examined to understand the meaning of the verse. The findings show that QS. al-Rūm [30]: 41 contains both theological messages and practical guidance for humanity to restore its relationship with nature. These noble values can be implemented through a simple and moderate lifestyle, the strengthening of environmental protection regulations, and the development of environmentally friendly technologies. Through these concrete steps, humankind can preserve the sustainability and balance of the earth for future generations.